Modeling the Sulfate Aerosol Evolution After Recent Moderate Volcanic Activity, 2008–2012. Issue 23 (3rd December 2021) - Brodowsky, Christina; Sukhodolov, Timofei; Feinberg, Aryeh; Höpfner, Michael; Peter, Thomas; Stenke, Andrea; Rozanov, Eugene
Abstract: Volcanic activity is a major natural climate forcing and an accurate representation of volcanic aerosols in global climate models is essential. This is a complex task involving many uncertainties in the model design and setup and observations. We analyze the performance of the aerosol‐chemistry‐climate model SOCOL‐AERv2 for three medium‐sized volcanic eruptions. We focus on the impact of differences in volcanic plume height and SO2 estimates on the stratospheric aerosol burden. The influence of internal model variability and dynamics are addressed through an ensemble of free‐running and nudged simulations at different vertical resolutions. Comparing the modeled evolution of the stratospheric aerosol loading to satellite measurements reveals a good model performance. However, a conclusive validation is complicated by uncertainties in observations and emission estimates. The large spread in emitted sulfur amount and its vertical distribution consequently lead to differences in simulated aerosol burdens. Varying tropopause heights among free‐running simulations add to these differences, modulating the amount of sulfur injected into the stratosphere. In nudged mode, volcanic aerosol burden peaks are well reproduced, however changes in convection and clouds affect SO2 oxidation paths and cross‐tropopause transport, leading to increased background burdens compared to observations. This effect can be reduced by leaving temperatures unconstrained. A higher vertical resolution of 90 levels increases the stratospheric residence time of sulfate aerosol by reducing the diffusion out of the tropical reservoir. We conclude that the model set‐up (vertical resolution and free‐running vs. nudged) as well as forcing parameters (volcanic emission strength and plume height) contribute equally to the model uncertainties. Key Points: Differences in estimates for volcanic emissions have a large effect on the aerosol evolution in SOCOL‐AERv2 Shifts in the tropopause cause variability in free running simulations while nudging leads to an elevated background sulfate aerosol burden An increased vertical resolution changes the diffusion of aerosols out of the tropical reservoir and therefore the lifetime